Reviewer Acknowledgements for the Special Edition at Global Health Management Journal: The 1st Special Edition of Cirebon International Health Symposium - GHMJ (Global Health Management Journal) (GHMJ (Global Health Management Journal))
Of more than 100 papers selected by the internal committees of the 1st Cirebon International Health Symposium, organized by Faculty of Medicine, Universitas Swadaya Gunung Jati, there are 24 papers will be featured in the 1st Special Edition of the Symposium, and published in GHMJ (Global Health Management Journal), Vol. 7, No.4, 2024 of the journal.